Relación entre la eficiencia del control interno y la gestión administrativa de la Municipalidad Distrital de San Juan Bautista en el periodo 2024 - Perez Alvan, Yasmina Lizeth (2025)
This research aims to analyze the relationship between the efficiency of internal control and administrative management in the District Municipality of San Juan Bautista during 2024. A quantitative approach was applied, with a non-experimental and correlational design, using Spearman’s correlation coefficient to measure the association between the variables. Data collected from a sample of 183 employees revealed a significant positive correlation between internal control and administrative management, indicating that the efficient implementation of internal controls directly influences the optimization of administrative processes. Furthermore, the study confirmed that the control environment, risk assessment, and internal communication are key factors in enhancing productivity and achieving strategic objectives. The findings highlight the importance of maintaining robust internal control systems aligned with daily operations to foster more efficient and transparent public management. This research concludes that internal control not only serves a supervisory function but also acts as a strategic tool that boosts administrative effectiveness and organizational performance within the municipality.